Pengaruh Literasi Pajak dan Sistem Administrasi Pajak Modern Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan di Era Digital pada Kota Medan - Fitri Handayani; Juliandi Sahputra; Ninis Waruwu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of tax literacy and a modern tax administration system on taxpayer compliance in paying land and building tax (PBB) in the digital era, particularly in Medan City. The research method used a quantitative approach, collecting data through questionnaires distributed to individual taxpayers in Medan City. Data analysis was conducted using multiple linear regression to examine the relationship between tax literacy and the modern tax administration system on taxpayer compliance levels. The results indicate that tax literacy has a positive and significant effect on taxpayer compliance, where increased tax understanding encourages awareness and compliance in fulfilling tax obligations. Furthermore, the implementation of a modern, digital-based tax administration system also positively contributes to simplifying the reporting and payment of land and building tax in Medan City. This study implies that improving tax education and modernizing the tax administration system are crucial for improving tax compliance in the digital era.